The global financial crisis and development: Whither Africa? - Augustin Kwasi Fosu (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
The global economic crisis beginning in 2008 has come at a very inopportune time for Africa. Sub-Saharan Africa (SSA) appeared to be on a march toward real economic and human progress, following the dismal performance of the 1980s and early 1990s. Economic growth had resurged since the mid-1990s, and was above the world average at the beginning of the early twenty-first century. Poverty had also declined considerably from their heights of the mid-1990s, rivaling the record over the same period for South East Asia and India, for instance. Meanwhile, human development had also resurged since the mid-1990s. Then the crisis hit. In response, growth fell by more than two-thirds. There appears to be some recovery, however, and the growth decline has so far been less than in previous economic crises, even though the global recession precipitated by the current crisis is the deepest since the Great Depression of the 1930s. SSA's apparent resilience this time around might be attributable to the improvement in its economic and political governance. Although the full economic and social impacts of the crisis are yet to be realized, with some uncertainty still in the global economic picture itself, the current evidence provides some hope that SSA may once again resume its path toward prosperity. Meanwhile, there is much variation across countries in their vulnerability to the crisis. Even though low-income and fragile countries appear to be holding up reasonably well, they may still require external assistance if they are to successfully weather the crisis.
Keywords: G01; O1; O55; 330; global financial crisis; development; Africa; Finanzmarktkrise; Entwicklung; Afrika